APPLICATION OF PANCASILA POCKET BOARD MEDIA IN PPKN SUBJECTS ON STUDENT LEARNING OUTCOMES IN CLASS II STATE 22 PRIMARY SCHOOL BANDA ACEH - Funna, Zuhra; Sulaiman, Sulaiman; Vitoria, Linda (Elementary Education Research, 2024)
In the learning process, teachers should use a variety of learning media, where by using learning media, students can more easily understand the learning delivered by the teacher so that they can achieve the expected learning outcomes. For this reason, a learning media can be applied that can make students active and responsive and further motivate students to participate in Civics learning. One of the learning media. that can be applied in PPKn learning is the Pancasila pocket board media. Based on the problem formulation, the researcher wants to know how the application of the Pancasila pocket board media in Civics subjects affects the learning outcomes of students in class II of SD Negeri 22 Banda Aceh. This research uses a qualitative approach with descriptive research type. The subjects of this research were 30 students in class II-A of SD Negeri 22 Banda Aceh. The data collection technique used in this research is by observing and giving test questions to students. Data were analyzed using data reduction, data presentation and drawing conclusions. As for the learning results obtained in class II-A of SD Negeri 22 Banda Aceh with a total of 30 students in the PPKn subject, there were 5 students who got incomplete grades, and 25 other students got complete grades. The average class score obtained was 81, which was greater than the KBM score of 70. This means that the use of Pancasila pocket board media can help the learning process to increase students' knowledge of the material. Thus, it can be concluded that the application of the Pancasila pocket board media can be used in Civics subjects.